Perancangan Interior Pusat Informasi Pemadam Kebakaran di Surabaya - Steven Anggreawan; Hedy Constancia Indrani; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
Surabaya Fire Department has important role to secure the safety of the city from fire disaster. Besides handling the wildfire, another role is to educate society about actions that cause wildfire and wildfire prevention. On the other hand, the society is lacking the interest of wildfire information. They believe that wildfire is hazardous and not supposed to be tried.In this design, the designer uses Design Thinking methods to find solutions and implements in the design. The design purpose is to create a fire department information center that does not exist in Surabaya as an education and recreation place for the people. This information center will be supported by some informative facilities such as information center, audio visual room and some simulation areas that can be used for practice directly, such as: smoke simulation, emergency simulation, VR simulation, emergency stairs simulation, sliding pole and fire simulation.